Management Practices of School Managers in Relation to the Secondary School Teachers’ Instructional Competence - Dela Cruz, Cecille; Batoon, Nerissa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between school managers’ management practices and teachers’ instructional competence in public secondary schools in the Division of Isabela. Anchored on the Human Relations Theory and the Instructional Leadership Framework, the study utilized a quantitative descriptive-correlational research design. Data were collected from 360 teachers and 35 school managers using validated questionnaires based on OPCRF and IPCRF indicators, and were analyzed using descriptive and inferential statistics, including weighted mean, Kruskal-Wallis test, Z-test, and Pearson correlation. Findings revealed that school managers demonstrated consistently outstanding performance and highly effective management practices, particularly in building connections and focusing on teaching and learning, although financial management emerged as a relative weakness. Teachers likewise exhibited very high instructional competence across all domains, with strengths in classroom management and content delivery, while ICT integration and inclusive strategies showed comparatively lower performance. Despite these high levels, the relationship between management practices and instructional performance was generally weak and statistically insignificant, indicating that teaching competence is largely independent and influenced more by individual skills and experience. The study concludes that targeted and practical professional development is necessary to address specific instructional gaps, particularly in ICT use and inclusive education. The study supports SDG 4 (Quality Education) by promoting improved teaching effectiveness and SDG 8 (Decent Work and Economic Growth) by strengthening workforce readiness through enhanced teacher competence. It contributes to sustainability by supporting institutional and educational development through improved leadership practices, professional growth, and evidence-based policy directions that enhance long-term school effectiveness and community outcomes.
Keywords: Educational Leadership; Instructional Competence; Management Practices; School Managers; Secondary Education; Secondary School Teachers; Teachers’ Performance